2018
DOI: 10.1007/s10902-018-9975-1
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Latent Satisfaction Reflected by Satisfaction Across Multiple Life Domains: A Prospective 32-year Follow-Up Study

Abstract: Intergenerational transmission of life satisfaction has been empirically established, but less is known about the continuity of satisfaction as being reflected across multiple life domains, unique effects of parental domain-specific satisfaction on offspring overall life satisfaction, and potential gender effects. In this population-based prospective study, the association between the life satisfaction of parents (G1) (2191 mothers and 2156 fathers) and their children (G2) (921 sons and 1277 daughters) was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…The Interdependence Theory [ 22 ] recognizes the importance of mutual influences (i.e., interdependence), while the Family Systems Theory [ 23 ] underscores the interdependence between individuals, so that individuals involved in reciprocal relationships, such as family members, can influence one another in their thoughts, emotions and behaviors. Consistent with these theories, research has shown that life satisfaction [ 14 , 24 ], job satisfaction [ 25 ], satisfaction with family life [ 14 , 26 ] and satisfaction with food-related life [ 14 , 27 ] are correlated between members of a couple. Therefore, both theories make it possible to hypothesize that an individual’s life satisfaction is not only influenced by their own satisfaction in different life domains but also by their partner’s satisfaction in different life domains in married or cohabiting couples, which, to the best of the authors’ knowledge, has not been previously assessed.…”
Section: Introductionmentioning
confidence: 97%
“…The Interdependence Theory [ 22 ] recognizes the importance of mutual influences (i.e., interdependence), while the Family Systems Theory [ 23 ] underscores the interdependence between individuals, so that individuals involved in reciprocal relationships, such as family members, can influence one another in their thoughts, emotions and behaviors. Consistent with these theories, research has shown that life satisfaction [ 14 , 24 ], job satisfaction [ 25 ], satisfaction with family life [ 14 , 26 ] and satisfaction with food-related life [ 14 , 27 ] are correlated between members of a couple. Therefore, both theories make it possible to hypothesize that an individual’s life satisfaction is not only influenced by their own satisfaction in different life domains but also by their partner’s satisfaction in different life domains in married or cohabiting couples, which, to the best of the authors’ knowledge, has not been previously assessed.…”
Section: Introductionmentioning
confidence: 97%
“…The findings above suggest that divergent life satisfaction levels may be found between families, and between members of a single family. Similar patterns of life satisfaction between family members have been explained by genetic personality traits (Carlsson et al, 2014;Dobewall et al, 2019;Headey et al, 2014;Thege et al, 2017), but also by family-related environmental aspects, such as parental influences, life events and shared experiences (Headey et al, 2014;Ma, 2016;Mauno et al, 2018;Thege et al, 2017). However, familyrelated environmental aspects may differ between families as well as affect in different ways the members of the same family.…”
mentioning
confidence: 94%
“…Family relationships contribute to SWB not only because they are included in the individual's overall assessment of their life, but because family members share characteristics and conditions that can account for similar assessments. In the case of life satisfaction, there is evidence indicating that life satisfaction levels are correlated between members of the same family (Carlsson, Lampi, Li, & Martinsson, 2014;Dobewall et al, 2019;Headey, Muffels, & Wagner, 2014;Ma, 2016;Maftei, Holman, & Cârlig, 2020;Mauno, Hirvonen, & Kiuru, 2018;Thege, Littvay, Tarnoki, & Tarnoki, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations